Development of sustainable mining strategies in Chile with a regionalized national model: Project introduction and overview - Maren Brandt; Loreto Bieritz; Anke Mönnig; Anett Großmann (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2017)
[Introduction] The research project “Development of sustainable strategies in the Chilean mining sector through a regionalized national model” inquires the socio-economic impacts of copper on the Chilean economy. The project is government-funded by the BMBF1 and supports the cooperation and exchange in knowledge between the Chilean team of Prof. Dr. Aroca and the GWS, a German company for empirical economic research. In September 2016, the project started and it is planned for a term of three years. Initially this discussion paper will introduce the joint research project and its question of interest. Afterwards basic information of Chile is given, this also includes a short summary about its economic history. Then the economic aspects of the mining sector will be presented and new economic, environmental and social challenges the Latin American country is facing will be discussed. The conclusion and the main results of this discussion paper are presented in the final section.
Keywords: 330